Constructing Santri’s Understanding of Religious Moderation within Islamic Boarding School Education - Siti Suwaibatul Aslamiyah; Dwi Aprilianto; Febriyanti, Trista; Nurista, Sindi (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This study aims to analyze the process of constructing santri's religious understanding of religious moderation in the context of Islamic boarding school education. Departing from the phenomenon of increasing religious polarization in Indonesia, Islamic boarding schools are positioned as strategic institutions in strengthening religious moderation. This study uses a social constructivism paradigm with an interpretive qualitative approach through a case study at the Al-Ikhlas Sedayulawas Brondong Lamongan Islamic Boarding School. Data were collected through participatory observation, in-depth interviews, focus group discussions (FGD), and document analysis, then analyzed using Miles and Huberman's interactive model with triangulation techniques to ensure data validity. The results show that santri's understanding of religious moderation is constructed through four intertwined dimensions, namely: (1) the cognitive-epistemological dimension, through the study of classical texts contextualized with the reality of nationality; (2) the socialinteractional dimension, through the example set by the kiai, dialogical learning patterns, and horizontal interactions among santri; (3) the cultural-institutional dimension, through rules, traditions, and pesantren culture that shape the habitus of moderation; and (4) the reflectiveagency dimension, which shows the active role of santri in reflecting on, negotiating, and internalizing the values of religious moderation. These findings confirm that students' understanding of moderation is not formed linearly through the transfer of knowledge alone, but through a dialectical and multidimensional process that involves daily experiences in pesantren life.